The Effect of Negative Product Publicity on Corporate Reputation Depending on the Degree of Crisis Responsibility, the Type of Consumer’s Self-construal and Product-involvement Level - 진용주; 유재웅; Yoon, Chun Suk (Asian Communication Research, 2019)
This study examines how seriously negative publicity about products affects corporate reputation in terms of the degree of direct corporate responsibility, product involvement level, and the type of consumer’s self-construal. The results show that negative media news coverage significantly harmed the corporate image. In particular, the corporate reputation was damaged more seriously when the corporate responsibility for public scandals were perceived to be high. However, corporate reputation was irrelevant to the product involvement. The people of interdependent construal or allocentric consumers responded more critically to the negative publicity and gave significantly lower grades to the companies that had a higher reputation for social responsibility. This study implements a two-by-two factorial design consisting of two different types of corporate responsibility and two types of product involvement. News articles with pictorial account depicting corporate behaviors were presented to on-line surveyees randomly. Theoretical and practical implications are suggested in the concluding section.
Keywords: Corporate crisis; Corporate reputation; Product involvement level; Corporate responsibility; Product characteristics